Missing persons : a critique of the social sciences - Douglas, Mary (Aaron Wildavsky forum for public policy ;, 1998)
The western cultural consensus based on the ideas of free markets and individualism has led many social scientists to consider poverty as a personal experience, a deprivation of material things, and a failure of just distribution. Douglas and Ney argue that the tradition of individualism applied to poverty and well-being is full of contradiction in light of anthropology's multicultural perspective. Douglas and Ney argue that the individualistic model of the person fostered in large part by economics has profoundly affected the ways in which we think about our needs and well-being. They offer a constructive suggestion for protecting objectivity in the social sciences by taking cultural variation into account. A multicultural context allows a far more evenhanded view of issues such as poverty and well-being. In Missing Persons, Douglas and Ney have set forth a fundamental critique of the social sciences, drawing from a vast array of literatures from anthropology, economics, political science, and sociology. All social scientists, particularly those concerned about poverty and well-being, will find this polemic essential. -- Provided by publisher.